Developing GeoGebra-based digital worksheets to foster conceptual understanding in circle geometry - Putu Friska Anandita; I Wayan Sudiarsa; I Gusti Agung Ngurah Trisna Jayantika (Universitas Hamzanwadi, 2026)
Digital tools are increasingly being used in mathematics learning; however, there are few empirical studies that have examined the effect of GeoGebra integration in structured learning media (e.g., digital worksheets) on students’ conceptual understanding in particular topics such as circles. This research aims to design and validate a digital worksheet using GeoGebra to improve students’ understanding of basic mathematical concepts. This study employed the Research and Development (R&D) approach using the ADDIE model. The subjects of the study were 48 students of Grade XI of a state senior high school in Gianyar, Bali, Indonesia. Data collection was conducted through expert validation, user evaluation, and concept understanding tests. Results showed that the developed digital worksheet was valid (average expert rating was above 4.2), practical (practically applicable on all indicators' evaluation), and effective, which was evidenced by a significant increase in student scores from pre-test (M = 73) to post-test (M = 87) with an N-Gain score of 0.68. Theoretically, this study contributes to the evidence of GeoGebra-supported conceptual learning in geometry, based on design-based research. Unlike its use as a standalone tool, the current study incorporates GeoGebra in structured worksheets to provide a guided-discovery framework for conceptual understanding.